Evaluasi Program Pembinaan Prestasi Atlet Persatuan Selancar Ombak Indonesia (PSOI) di Kota Padang - Ilpake Pasca; Anton Komaini; Yanuar Kiram; Arsil Arsil; Masrun Masrun (Jurnal Sporta Saintika, 2026)
His study aims to examine the implementation of the Indonesian Surfing Association (PSOI) athlete performance development program in Padang City from four perspectives: context, input, process, and product. This is a program evaluation study using the CIPP (Context, Input, Process, and Product) method. The study was conducted at the Indonesian Surfing Association (PSOI) Club in Padang. The subjects of this study consisted of the chairman, coaches, and athletes. Data were collected through observation, interviews, and documentation. The research results indicate that first, the objective of the training program is to prepare athletes for upcoming competitions. Second, the program includes training sessions, coaches, and athletes, as well as adequate facilities and infrastructure. Third, there is a written training plan covering physical, technical, and tactical components, along with supervision by coaches; however, there is a lack of oversight from management. Fourth, there is an improvement in the athletes’ attitude and quality of play. Fifth, the program has been successful and shows improvement compared to before, but still requires refinements; overall, the training program can be continued with some improvements.